Critical Success Factor (CSF) of Implementing PPP Road Sector in Indonesia - Dody Kurnia Lumban Gaol; Ratna Ayu Damayanti; Andi Kusumawati (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
The MPWH of Indonesia has a role in the development of road projects. Road projects require a large number of funds. One of the funding schemes currently being pursued by the government to overcome this funding gap is Public Private Partnership (PPP). The implementation of the PPP requires a lot of attention from various parties so that the project runs well. The purpose of this study is to examine the priorities of CSF in the implementation of PPP in the Road Sector in Indonesia. This study used questionnaires and analysis used mean score & RII. There are 45 samples of private sectors and 5 governments. The results of the study show that strong commitment from the government during the PPP implementation, clear PPP regulations, transparent and competitive procurement process are the top three success factors of the PPP road sector in Indonesia. CSF can provide an overview to governments and private sectors in the implementation of the PPP Road Sector in Indonesia. A strong commitment from governments and private sectors is expected to minimize the risk of project failure.